First field efficacy trial of the ChAd63 MVA ME-TRAP vectored malaria vaccine candidate in 5-17 months old infants and children - Tiono, Alfred B.; Viebig, Nicola; Leroy, Odile (PLOS ONE, 2018)
Background Heterologous prime boost immunization with chimpanzee adenovirus 63 (ChAd63) and Modified Vaccinia Virus Ankara (MVA) vectored vaccines is a strategy previously shown to provide substantial protective efficacy against P. falciparum infection in United Kingdom adult Phase IIa sporozoite challenge studies (approximately 20-25% sterile protection with similar numbers showing clear delay in time to patency), and greater point efficacy in a trial in Kenyan adults. Methodology We conducted the first Phase IIb clinical trial assessing the safety, immunogenicity and efficacy of ChAd63 MVA ME-TRAP in 700 healthy malaria exposed children aged 5-17 months in a highly endemic malaria transmission area of Burkina Faso. Results ChAd63 MVA ME-TRAP was shown to be safe and immunogenic but induced only moderate T cell responses (median 326 SFU/106 PBMC (95% CI 290-387)) many fold lower than in previous trials. No significant efficacy was observed against clinical malaria during the follow up period, with efficacy against the primary endpoint estimate by proportional analysis being 13.8% (95%CI -42.4 to 47.9) at sixth month post MVA ME-TRAP and 3.1% (95%CI -15.0 to 18.3; p = 0.72) by Cox regression. Conclusions This study has confirmed ChAd63 MVA ME-TRAP is a safe and immunogenic vaccine regimen in children and infants with prior exposure to malaria. But no significant protective efficacy was observed in this very highly malaria-endemic setting. Trial registration ClinicalTrials.gov NCT01635647. Pactr.org PACTR201208000404131.